Management commitment and awareness creation – ICT safety and security in electric power supply network companies. (13th July 2015) - Skotnes, Ruth Østgaard
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to follow-up on previous research by studying the degree of management commitment to information and communication technology (ICT) safety and security within network companies in the electric power supply sector, implementation of awareness creation and training measures for ICT safety and security within these companies and the relationship between these two variables. Design/methodology/approach – Data were mainly collected through a survey among users of ICT systems in network companies within the Norwegian electric power supply sector. In addition, qualitative data were gathered through interviews with representatives from the regulatory authorities, and observation studies were conducted at ICT safety and security conferences. Findings – In accordance with previous research, our survey data showed a statistically significant correlation between management commitment to ICT safety and security and implementation of awareness creation and training measures. The majority of survey respondents viewed the degree of management commitment to ICT safety and security within their own organization as high, even though qualitative studies showed contradictory results. The network companies had implemented awareness creation and training measures to a varying degree. However, interactive awareness measures were used to a lesser extent than formal one-way communication methods. Originality/value – The paper provides insight into management commitment to and implementation of awareness creation and training measures for ICT safety and security within network companies.